BICUBIC-BASED PIXEL ESTIMATION TECHNIQUE FOR IMAGE ENHANCEMENT ON CLOSE CIRCUIT TELEVISION - Kingboo, Athaporn; Maliyaem, Maleerat (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The Close Circuit Television (CCTV) is a great device for recording awholesome moving well, it can be used to record events that occur at any time. However, the ability for recording events is good, but the image captured from CCTV, is in terms of quality and sharpness, depends on the performance and features of the CCTV system. A good quality of CCTV is more expensive than low-quality of CCTV in terms of resolution. It caused of installation cost respectively. This research proposed an image enhancement technique for low-quality CCTV, in terms of resolution and sharpness, using the Bicubic-based Pixel Estimation (BPE) technique. The experiments are conducted using by a set of enlarged image. The results show an overall average of PSNR is 19.341 and SSIM is 0.179 which out well than other techniques. Our experimental results show our proposed algorithm outperformed others’ in terms of quality and sharpness.